PREFERENSI KONSUMEN PADA MEREK PAKAIAN ROPU MENGGUNAKAN ANALISA KONJOIN - Desy Permana Sari; Liliana Dewi (STIE Mahardhika, 2020)
Wear Saoirse is a company that runs in the fashion industry. The main product of Wear Saoirse is a casual dress with Ropu brand. Wear Saoirse has not been able to maximize the existing opportunities and has experienced failure in running business. The purpose of this research is to determine what clothing product attributes whether are considered the most important for prospective consumers and determine what combination of clothing product attributes that are requested by prospective consumers in which those preferences are measured from the attributes of price, comfort, style, color, and fabric type. This research uses descriptive quantitative research with quantitative approach and conjoint analysis. The population of this research is the Tuban people, females, and age between 18 to 30 years old and the sample that taken is 97 people based on Wibisono formula. The sampling collection technique is purposive sampling. Data collection is done using questionnaire. The result of this research shows that clothing product attributes that are considered the most important by respondents are comfort attribute and color attribute and the combination of requested clothing product attributes, that is, clothing products from the price of 125,000 to 149,999, with comfort, that is, loose, the style that suits trend, soft color, and fabric type, that is, cotton.